1984
DOI: 10.1080/01688638408401227
|View full text |Cite
|
Sign up to set email alerts
|

Base rate data for the WAIS-R: Test-Retest stability and VIQ-PIQ differences

Abstract: The data analyzed were the 14 WAIS-R scores from each of the individuals who comprised the WAIS-R standardization sample. Examined was the individual VIQ-PIQ difference from only the initial examination of each of the 1880 subjects, as well as the test-retest change in each of the 14 WAIS-R scores for each of the 119 subjects who were retested. The results revealed that, although the WAIS-R has excellent psychometric reliability as reflected in its standard error of measurement of a VIQ-PIQ difference and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
114
0
5

Year Published

1985
1985
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 169 publications
(125 citation statements)
references
References 7 publications
6
114
0
5
Order By: Relevance
“…Matarazzo and Herman (1984) demonstrated that although a 10-point split may be reliable statistically, it is not statistically uncommon. That is, 38.8% of the normal population has a VIQ-PIQ split of 10 or more points.…”
mentioning
confidence: 96%
“…Matarazzo and Herman (1984) demonstrated that although a 10-point split may be reliable statistically, it is not statistically uncommon. That is, 38.8% of the normal population has a VIQ-PIQ split of 10 or more points.…”
mentioning
confidence: 96%
“…Only a sufficiently large and representative sample then can warrant a satisfactory approximation. In recent years, base rate information on change gathered within normative populations is being increasingly published Matarazzo & Herman, 1984;McSweeny et al, 1993;Temkin et al, 1999). The present article discusses three variants of estimating the standard error of the JT and the Chelune et al indices encountered in research reports.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] DSST score provides an integrative measure of visuomotor coordination, processing speed, and short-term memory. 20 It is possible that low DSST score denotes a deficit reflecting ''slowness'' of cognitive function, which might directly impact health to increase mortality risk (e.g., inability to follow medication schedules). 16 Alternatively, low DSST score may signal the presence of other health problems possibly outside the central nervous system itself, such as vascular or metabolic disease.…”
Section: Discussionmentioning
confidence: 99%